Epidemiologic challenges in norovirus vaccine development. Issue 6 (3rd June 2019) - Hallowell, Benjamin D.; Parashar, Umesh D.; Hall, Aron J.
ABSTRACT: Norovirus is the leading cause of acute gastroenteritis (AGE) worldwide. In the United States norovirus is estimated to cause 19–21 million illnesses, 1.7–1.9 million outpatient visits, 56, 000–71, 000 hospitalizations, and 570–800 deaths annually. Through direct costs and loss of productivity, norovirus disease cost the US economy more than $5.5 billion annually. Due to the lack of available therapies to treat norovirus infections and their highly infectious nature, preventing norovirus illness through vaccination is an appealing strategy. Currently, several norovirus vaccines are in development, including five vaccines in preclinical trials, an oral monovalent vaccine (Vaxart, Inc.) that recently completed a phase IB clinical trial, and a bivalent intramuscular vaccine (Takeda Pharmaceutical Company Limited) in a phase IIB clinical trial. However, no norovirus vaccines are currently available on the market. In this commentary we aim to describe some of the barriers faced in norovirus vaccine development, particularly focusing on vaccine effectiveness and defining the target population.